Influence of deposition time on the structure and optical properties of CuGaO2 thin films - Saturi Baco; Nur Asilah Mohd Adnan; Nur Alfatini Suhardi; Rubena Yusoff; Chee, Fuei Pien; Saafie Salleh; Afishah Alias (Faculty of Science & Natural Resources, UMS, 2024)
Copper gallium oxide (CuGaO2) is a transparent p-type semiconductor with a wide bandgap, making it highly relevant for semiconductor technology. This study explores how deposition time impact the structure and optical properties of CuGaO2 thin films. Using radio frequency magnetron sputtering, the films were deposited on the glass substrate with deposition times ranging from 30 to 120 minutes. The grain size of the films was analyzed using X-ray diffraction (XRD), which revealed that the films remained amorphous regardless of the deposition time. However, optical characteristic measured by UV-VIS Spectrophotometer indicated that extending the deposition time from 30 minutes to 90 minutes increased the bandgap from 2.27 eV to 2.68 eV.